Development of food electronic nose for prawn (macrobrachium rosenbergii) quality rapid assessment and their relationship with the physicochemical index. Issue 1 (1st January 2021) - Jiang, Chenhao; Ning, Jingyuan; Mei, Zhenghao; Chen, Jiaqi; Gao, Yuanyuan; Yi, Xiaomei; Wu, Peng
ABSTRACT: Construction of food electronic nose (FEN) for prawn ( Macrobrachium rosenbergii ) quality rapid assessment assisted with physicochemical parameters was explored in this paper. Sensory analysis, weight, GC/MS, and K value, and microbial were examined to provide the assisting basis for FEN system design. Results indicated that sensory acceptance decreased with the increase in time. The decline of prawn physiochemical parameters was associated with microbiological propagation. The volatile gases emitted by prawn could be utilized for sample quality characterization. FEN successfully discriminated all samples, and presented good detecting accuracy. The method proposed in this work is promising in aquatic products quality rapid analysis.